Private sector firms, social responsibility and poverty reduction: Evidence from Cambodia. Issue 1 (3rd May 2016) - Hipsher, Scott
Abstract : Purpose: The purpose of this paper is to explore the perspectives of workers in one of the least developed economies (Cambodia) on the creation of new job and livelihood opportunities created by foreign firms or foreign investment. Design/methodology/approach: Qualitative: randomly selected interviews of individuals. Findings: Individuals working in international organizations find international business activities increase their livelihood options and therefore help to improve their lives. Research limitations/implications: An exploratory approach using convenience sampling was taken which limits generalizing the results to a broader population. Practical implications: The concepts explored can be used by individual firms when formulating their social responsibility programmes and the ethical implications of their business practices in emerging markets as well as by governments in creating public policies concerning poverty reduction. Social implications: Presents and respects the views of lower income individuals working in the tourism industry whose voices are often overlooked when corporate social responsibility and public policies are designed. Originality/value: Provides a perspective about poverty reduction of individuals from low-income backgrounds whose lives are directly impacted by international investment and trade.